2022
DOI: 10.18702/acf.2022.6.8.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of advanced computational techniques for estimating the compressive strength of UHPC

Abstract: The effect of raw materials on the compressive strength of concrete is a complex process, especially in the case of ultra-high-performance concrete (UHPC), where a higher number of inter-dependent parameters are involved in the strength development. In this era of digitalization, advanced machine learning methods are used to predict the material's mechanical characteristics because of their superior performance compared to conventional and nonlinear statistical regression models. Thus, the goal of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 34 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…There are some new prediction approaches [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], such as adaptive neuro-fuzzy inference system (ANFIS), deep learning (DL), marine predators algorithm (MPA), pure random orthogonal search (PROS), artificial neural networks (ANNs), genetic algorithm (GA), and particle swarm optimization (PSO) method, etc. These approaches can better reveal the strength of structures in a more unbiased way, which should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There are some new prediction approaches [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], such as adaptive neuro-fuzzy inference system (ANFIS), deep learning (DL), marine predators algorithm (MPA), pure random orthogonal search (PROS), artificial neural networks (ANNs), genetic algorithm (GA), and particle swarm optimization (PSO) method, etc. These approaches can better reveal the strength of structures in a more unbiased way, which should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to predict concrete strength characteristics [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Machine learning methods are employed to forecast concrete strength [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and the durability of concrete [ 50 , 51 , 52 ]. Bagging regression (BR) and gradient boosting (GB) models based on a variation of the bootstrap aggregation decision tree (DT) method have been shown in several studies to outperform other stand-alone ML models in terms of concrete strength prediction accuracy [ 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Steel, artificial, and natural fibers are incorporated into concrete to enhance the mechanical properties and resistance against cracks of cementitious concrete composites [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Different studies have been conducted on models for regular concrete mechanical properties depending on a wide database [ 16 ], although there are additional predicting parameters such as fiber type, aspect ratio, and volumetric content for SFRC compared to normal concrete. However, the development of appropriate predictive models is still new.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the scuffling of conventional nonlinear and linear regression models is used to determine the compressive strength of SFRC. ML techniques may assist in resolving the issue of difficulty for the strength prediction of SFRC [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Although multiple experimental studies have been conducted for this purpose, as reported in the literature, the prediction of SFRC properties having different mix design components is still quite hard.…”
Section: Introductionmentioning
confidence: 99%